2015
DOI: 10.1111/nmo.12585
|View full text |Cite
|
Sign up to set email alerts
|

Rome III functional dyspepsia subdivision in PDS and EPS: recognizing postprandial symptoms reduces overlap

Abstract: EPS and PDS symptoms frequently coexist in FD patients, with postprandial symptoms substantially contributing to the overlap. A more rigorous linking of postprandially occurring symptoms to PDS, regardless of their qualitative nature, may improve the separation between PDS and EPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 31 publications
4
53
0
Order By: Relevance
“…Although replication of our results is needed, revisions of the existing classification system (currently Rome III) should to take into account that, at least in tertiary care, FD may represent one single rather than two distinct syndromes, as also suggested by earlier data demonstrating frequent overlap between EPS and PDS in tertiary care . However, recent findings indicate that defining PDS based on postprandial nature of symptoms rather than based on distinct symptom profiles per se significantly reduces this overlap . Further, our current factor analytical results do identify distinct symptom‐based factors corresponding to Rome III subgroups, which may be driven by distinct underlying pathophysiological mechanisms.…”
Section: Discussionsupporting
confidence: 70%
“…Although replication of our results is needed, revisions of the existing classification system (currently Rome III) should to take into account that, at least in tertiary care, FD may represent one single rather than two distinct syndromes, as also suggested by earlier data demonstrating frequent overlap between EPS and PDS in tertiary care . However, recent findings indicate that defining PDS based on postprandial nature of symptoms rather than based on distinct symptom profiles per se significantly reduces this overlap . Further, our current factor analytical results do identify distinct symptom‐based factors corresponding to Rome III subgroups, which may be driven by distinct underlying pathophysiological mechanisms.…”
Section: Discussionsupporting
confidence: 70%
“…12 Investigation on the effect of meal ingestion on symptom generation has indicated that in patients with dyspepsia, not only postprandial fullness and early satiation, but also epigastric pain or epigastric burning sensation and nausea (not vomiting) may increase after the meals. Carbone et al 13 in Belgium reported that by accounting the relationship between epigastric pain and nausea in relation to meal ingestion, symptoms of PDS and EPS frequently coexist in patients with FD, and then postprandial symptoms substantially contributes to the overlap in the previous Rome III definition. Then they demonstrated that a more rigorous link of symptoms after meals to PDS might improve the separation efficiency of PDS from EPS.…”
Section: Epigastric Pain Syndrome May Coexistmentioning
confidence: 99%
“…Then they demonstrated that a more rigorous link of symptoms after meals to PDS might improve the separation efficiency of PDS from EPS. 13 Accordingly, the definition of PDS was slightly revised by including that, in addition to postprandial fullness and early satiety that is known to occur postprandially, other symptoms such as epigastric pain and burning can be occurred or modified also by ingesting a meal (Table). 4 In addition, epigastric bloating, belching, and nausea can be present in both PDS and EPS as possible adjunctive features of both, while vomiting is unusual, and should prompt a search for other diagnoses such as nausea and vomiting disorder.…”
Section: Epigastric Pain Syndrome May Coexistmentioning
confidence: 99%
“…In this issue of Neurogastroenterology and Motility, the research group of Tack evaluated 199 patients with FD selected from 1029 patients presenting for endoscopy . Consistent with previous outpatient studies, PDS was more frequent than EPS but the overlap group with both PDS and EPS was the most prevalent.…”
mentioning
confidence: 76%